Review of Tertiary coal fields of lower Indus plain in Pakistan and adjacent areas of Gujrat and Rajasthan states in India - Durrani, Nasir Ali (Journal of Himalayan Earth Sciences, 1992)
This paper discusses possible occurrences of lignite in a large area of Lower Indus Plain, especially in the desert areas of Thar Parker district and extending over to areas of Gujrat and Rajasthan states in India. Review of available geologic publications, drilling data and projections from known coal fields of southern Sindh in Pakistan and Gujrat and Rajasthan States in Western India, including reports of coal intercepted by Oil and water drilling companies in these areas and a recent discovery of 12 to 13 meter thick lignite coal seam just south of Chachro in Thar Parker, now reasonably substantiate the idea that Thar Parker desert is underlain by vast resources of unexplored coal deposits.